2015
DOI: 10.21106/ijma.51
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Health Care Quality Indicators among US Children with Special Health Care Needs According to Household Language Use

Abstract: Background:Lower health care utilization and less favorable health outcomes have been demonstrated in children from Non-English Primary Language households (NEPL) in previous studies. This study examines prevalence of health care quality indicators among US children with special health care needs (CSHCN) and their association with household language use.Methods:We used data from the 2009-2010 National Survey of Children with Special Health Care Needs, restricted to an analytic sample of 40,242 children. Logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In particular, results for households in which English is not the primary language suggest a continued need for medical interpretation and translation services to improve the provision of FCC and to facilitate family-professional partnerships. 18,24 In addition, we found that having a PDN was the subcomponent with the lowest attainment rate among non-CSHCN (71%). One possibility is that non-CSHCN could be more likely to use large group, urgent care, or school-based practices in which they are less likely to see the same clinician each time.…”
Section: Discussionmentioning
confidence: 75%
“…In particular, results for households in which English is not the primary language suggest a continued need for medical interpretation and translation services to improve the provision of FCC and to facilitate family-professional partnerships. 18,24 In addition, we found that having a PDN was the subcomponent with the lowest attainment rate among non-CSHCN (71%). One possibility is that non-CSHCN could be more likely to use large group, urgent care, or school-based practices in which they are less likely to see the same clinician each time.…”
Section: Discussionmentioning
confidence: 75%
“…Yet to date, studies on language-related oral health disparities have focused primarily on children. Children in non-English primary language households are more likely to be poor, overweight (Flores & Tomany-Korman, 2008), and lack oral health care (Yu et al, 2015). No study to date has focused on potential variations in oral health among adult non-English speakers, exploring the interlocking roles of nativity and English proficiency and whether the barriers are similar at different levels of socioeconomic status, which is what this study undertakes herein.…”
Section: Background and Significancementioning
confidence: 99%
“…Research show these groups lack access to SDM and, once they access it, they report lower quality in their SDM experiences compared with white families. 12-15…”
Section: Introductionmentioning
confidence: 99%
“…Research show these groups lack access to SDM and, once they access it, they report lower quality in their SDM experiences compared with white families. [12][13][14][15] A systematic literature review showed variation in how racial and ethnic minority groups experience SDM in health care settings. 16 Reviewed studies reported that some minority patients do not feel comfortable being expected to actively engage in decision making with a clinician in the early stages of the clinical process while trust and familiarity with the particular health condition(s) were developed.…”
mentioning
confidence: 99%